The Tahfidzul Qur'an Program and Cultural Communication: Improving School Image - Zamroni; Hasan Baharun; Intan Dewi Rukmana (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to examine "Building a Positive Image of the School Through the Tahfidzul Qur'an Program in the Perspective of Cultural Communication" using a qualitative with case study. At SMPN 1 Kotaanyar, researchers observed, interviewed, and documented. Islamic society, in general, with different races and ethnicities, has the same goal: to want their sons and daughters to continue studying and deepen their knowledge of the Qur'an. Thus SMPN 1 Kotaanyar provides a program of tahfidzul Qur'an in order to build a positive image of the school from this perspective. Cultural communication. Based on research conducted at SMPN 1 Kotaanyar through the tahfidzul Qur'an program, which was carried out to build a positive image of the school from a cultural communication perspective by making an attractive logo as a brand, promoting the institution through the availability of social media, and increasing the value of students and perspective alums quality and Qur'anic soul.